Juvenile Delinquency among Children and Its Effects (Archives of Criminology, 2006)
The object of study was prohibited acts committed by children up to 13 years  old which caused a reaction of the justice system. The results of the research deny a common belief, also popularised by the mass media that the age of juveniles who committed serious crimes is rapidly falling down. In fact, in most cases we deal with petit crimes.